Analysis of service quality dimensionscompetitive advantage at the samsat office of palangka raya city - Robert Coven (International Journal on Social Science, Economics and Art, 2024)
Services to the community play a very vital role in community development, and SAMSAT as a form of public service, including SAMSAT Palangka Raya City, has an important role in providing services to taxpayers. This research proposes the hypothesis that Quality of Service to the Public has the potential to increase SAMSAT's competitive advantage. The research method used is quantitative by applying SEM PLS analysis techniques. The research results show that the quality of service to the public has a significant influence on the competitive advantage of SAMSAT Palangka Raya City. Data analysis yielded a very low P value (0.000), indicating a high level of statistical significance. These findings strengthen the argument that improving the quality of public services in SAMSAT can be considered a crucial strategy to maintain and improve competitive position in the market.